Carbohydrate content and ingredient profile of supposedly “low-carb” food products in Brazil - Junco, Rodrigo Cavalcante; Prates, Sarah Morais Senna; Anastácio, Lucilene Rezende (Nutrition and food science, 2023)
Purpose This study aims to evaluate the carbohydrate content, ingredient profile and degree of processing of supposedly “low-carb” foods in the Brazilian market. Design/methodology/approach Information was collected from physical supermarkets in Divinópolis, Minas Gerais and on websites throughout Brazil between July and September/2020. The carbohydrate content was assessed in g/100 g, and ingredient lists were investigated for the presence of carbohydrate-rich ingredients. The degree of processing of the products was evaluated by NOVA classification to determine whether the term “low carb” had been translated into Portuguese. Findings This study evaluated a total number of 164 products, the most frequent were bakery products (34.7%), granola and cereal bars (19.5%) and candies and desserts (14.0%). This claim was also found in low-carb foods such as cheese and chicken. Most food products evaluated (56.0%) were classified as ultra-processed, with the group having the highest carbohydrate content (20.0; 3.0–47.5g/100g), compared to products classified as processed foods (p < 0.01). The ingredient lists showed items rich in carbohydrates, such as cassava and corn derivatives. In 162 products, a low-carb claim was displayed without translation into Portuguese. These data demonstrate that most of these products are ultra-processed and have a high glycidic content. Originality/value To the best of the authors’ knowledge, the study was a pioneer investigation of the ingredients of “low-carb” foods, their carbohydrate composition and their degree of processing based on the NOVA classification.